Refractory, missed and severe Kawasaski disease: Diagnostic and therapeutic challenges - Comitis, George; Lawrenson, John; Van Schalkwyk, Adre; Zühlke, Liesl (SA Heart Journal, 2017)
Kawasaki disease (KD) is an acute generalised vasculitis of childhood with a predilection for the coronary arteries causing ectasia and aneurysms with subsequent potential ischaemic heart disease and even sudden death. This risk is signifi cantly reduced by early treatment with intravenous immunoglobulin together with a high dose of aspirin. However, the diagnosis is often diffi cult to make as many childhood illnesses may mimic KD. In addition, presentations may be atypical or incomplete. We discuss a series of 3 recent cases to focus on the management of 3 potentially troublesome aspects of the disease namely: severe coronary vascular involvement, failure to recognise the disease and disease which is refractory to standard therapy. We will also provide a suggested treatment algorithm for refractory KD with reference to current and future research strategies.